2009
DOI: 10.1080/01639360903140338
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Energy Deficiency in Rural-Dwelling Older Indian Adults During a Period of Severe Drought

Abstract: The prevalence of chronic energy deficiency (CED = BMI < 18.5) among older adults (≥60 years) was assessed utilizing a large data set from a community-based cross-sectional study carried out in severely drought-affected rural areas of India. Anthropometric measurements (height, weight) were recorded for a total of 3,147 individuals, and a family diet survey (one day 24-hour recall) was carried out in 1,900 households (HHs) from 190 villages. As per the Body Mass Index (BMI), the prevalence of CED was 51.1% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Few other studies have been undertaken to assess the relationship between farming and CED. One cross-sectional study conducted during drought in 1347 rural Indian adults provided evidence for a higher prevalence of CED in individuals at socioeconomic disadvantage and in households engaged in marginal and small sized farming [28]. In a survey, based on data from the 2005/06 National Nutrition Survey across twenty major Indian states, improved agricultural performance was found to markedly reduce the risk of CED in adults and body wasting in young children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have been undertaken to assess the relationship between farming and CED. One cross-sectional study conducted during drought in 1347 rural Indian adults provided evidence for a higher prevalence of CED in individuals at socioeconomic disadvantage and in households engaged in marginal and small sized farming [28]. In a survey, based on data from the 2005/06 National Nutrition Survey across twenty major Indian states, improved agricultural performance was found to markedly reduce the risk of CED in adults and body wasting in young children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Subasinghe et al (2014) found that subsistence farming was strongly associated with CED in south Indian men and women. Arlappa et al (2009) provided evidence for a higher prevalence of CED in individuals at socioeconomic disadvantage and in small and marginal farmer households, while Gulati et al (2012), using data from the National Family Health Survey 2005-06 (NFHS-3) and national accounts, reported that improved agricultural performance markedly reduced the risk of CED in adults and can have a positive impact on nutritional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All studies suggested that farmers had higher prevalence of underweight than homemakers, [36] manual and non-manual women [38]; business, [39] government and non-government [36] women and men; and 'other' (than non-agricultural) workers in analyses combining genders. [37] The prevalence of underweight was higher among farming than among self-employed men but not women. [36] Underweight was more prevalent among farmers than among unemployed women, [38] but similar to students, retired and unemployed people (the latter two were combined in gender-specific analyses).…”
Section: Plos Onementioning
confidence: 95%
“…The longitudinal study followed up participants 10 years from baseline. The cross-sectional studies comprised eight analyses of primary data [30][31][32][33][34][35][36]; two secondary analyses of existing cross-sectional data [37,38]; and three cross-sectional analyses of longitudinal data, [39][40][41] of which two used data from different time points of one study. [40,41] Study settings and characteristics differed substantially between studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation